Heart regeneration in the salamander relies on macrophage-mediated control of fibroblast activation and the extracellular landscape - Godwin,JW; Debuque,R; Salimova,E; Rosenthal,NA (npj Regenerative Medicine, 2017)
In dramatic contrast to the poor repair outcomes for humans and rodent models such as mice, salamanders and some fish species are able to completely regenerate heart tissue following tissue injury, at any life stage. This capacity for complete cardiac repair provides a template for understanding the process of regeneration and for developing strategies to improve human cardiac repair outcomes. Using a cardiac cryo-injury model we show that heart regeneration is dependent on the innate immune system, as macrophage depletion during early time points post-injury results in regeneration failure. In contrast to the transient extracellular matrix that normally accompanies regeneration, this intervention resulted in a permanent, highly cross-linked extracellular matrix scar derived from alternative fibroblast activation and lysyl-oxidase enzyme synthesis. The activation of cardiomyocyte proliferation was not affected by macrophage depletion, indicating that cardiomyocyte replacement is an independent feature of the regenerative process, and is not sufficient to prevent fibrotic progression. These findings highlight the interplay between macrophages and fibroblasts as an important component of cardiac regeneration, and the prevention of fibrosis as a key therapeutic target in the promotion of cardiac repair in mammals.